2005
DOI: 10.2298/sarh0502029f
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk factors in premature infants with respiratory distress syndrome treated by mechanical ventilation

Abstract: In spite of the implementation of high technology in Neonatal Intensive Care in our country, the mortality rate of the infants with RDS is high, but is not different from that in developing countries. The improvement of perinatal care and diminution of risk factors, common use of surfactant as well as antenatal steroids could most probably result in better outcome of neonatal RDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
3
5
0
6
Order By: Relevance
“…In compatible to our results Arit demonstrated much of the mortality rate in neonates with low gestational age and low birth weight [13]. Fidanovski also detected higher risk of mortality in infants with lower birth weight and shorter gestational age in 126 premature infants hospitalized at Pediatric Intensive Care Unit [15].…”
Section: Discussionsupporting
confidence: 89%
“…In compatible to our results Arit demonstrated much of the mortality rate in neonates with low gestational age and low birth weight [13]. Fidanovski also detected higher risk of mortality in infants with lower birth weight and shorter gestational age in 126 premature infants hospitalized at Pediatric Intensive Care Unit [15].…”
Section: Discussionsupporting
confidence: 89%
“…10,11 The study observed 27% newborn have had severe respiratory distress which was less as compared to study conducted by Derek C. 12 Study also revealed max, 57.14% newborn developed severe respiratory distress had low APGAR score. Similar findings have also been reported by Lureti M et al, Fidanovski D et al and Gouyon J et al 13,14,9 Our study observed that max 15,16 Primi para was significantly associated with respiratory distress has been reported by Dani C et al, whereas multipara noted by Mathur N et al 15,17 The caesarean mode of delivery was associated for newborn respiratory distress mentioned by Dani C et al, Geller E et al and Gouyon J et al, respectively. 9,15,18 Low gestational age at the time of delivery was a risk factor for respiratory distress also observed by Dani C et al, and Lureti M et al 13,15 The studies conducted by Lureti M et al and Miller H et al, also mentioned that low birth weight is a risk factor for respiratory distress among newborn baby.…”
Section: Discussionsupporting
confidence: 89%
“…Prematurez extrema, neonato con los siguientes hallazgos en la autopsia: desarrollo pulmonar en fase canalicular (16-24 semanas) y signos morfológicos de hipoxia fetal aguda intrauterina (9). Enfermedad de membrana hialina, neonato con distrés respiratorio, requerimientos de O2 aumentado, radiología compatible y hallazgos de membranas hialinas en bronquiolos terminales, alvéolos y atelectasias (25). Hipoplasia e inmadurez pulmonar en gestaciones menores de 24 semanas, habitualmente con rotura prematura de membranas de inicio precoz y desarrollo pulmonar en fase canalicular en la autopsia (26).…”
Section: Pacientes Y Métodosunclassified